Stranger rape; distinctions between the typical rape type and other types of rape. A study based on data from Center for Victims of Sexual Assault. (May 2021) - Friis-Rødel, Anne Mie; Leth, Peter Mygind; Astrup, Birgitte Schmidt
Abstract: Objective: The aim of this descriptive cohort study was to characterize stranger rape compared to other types of rape. Method & Materials: All cases of women aged 12 years or older, who contacted a Center for Victims of Sexual Assault in the region of Southern Denmark and underwent a forensic examination in 2018, were collected and analyzed. Descriptive frequencies, Pearson's χ 2 -test and Fisher's exact-test were performed. Results: Compared to other types of rape, stranger rape were reported to the police more frequently, earlier and more frequently independently, without contact to family, friends or other authorities. In cases of stranger rape women were exposed to threats and violence more often, and clinical findings were found to coincide with the women's report more frequently. Regarding the offenders' level of planning, it was not possible to find significant differences between stranger rape and other rape types by comparing frequencies of the offenders' use of condoms and weapons and/or other remedies as surrogate markers for degree of planning. Conclusion: There were several significant characteristic differences between stranger rape and other types of rape . Characterizing the 'archetypical rape' in opposition to other and more frequent types of rape, may give the public, the police, the courts and aid organizations the background needed to understand the importance of rape typologies when handling cases of sexual assault. Highlights: Victims of stranger rape reported significantly more often directly to the police instead of involving a third party. Victims of stranger rape more often reported to the police immediately without delay, than victims of other types of rape. Victims of stranger rape were more often exposed to threats and to violence than victims of other types of rape.